BIOECOLOGICAL FEATURES OF THE MEDICINAL SMALL-FLOWERED MOUNTAIN BASIL (ORIGANUM TYTTANTHUM L.) - Boboyeva Hurshida Burhonovna (Western European Studies, 2025)
The introduction and bioecological characteristics of the medicinal small-flowered mountain oregano, Origanum tyttanthum L., were studied under the climatic and soil conditions of the Samarkand oasis. These scientific investigations aimed to enrich the local flora with diverse medicinal plants and meet the increasing demand of the regional pharmaceutical industry for raw materials by introducing a promising medicinal species. Field experiments on seed propagation of Origanum tyttanthum L. were conducted in typical gray soil climate conditions of the Samarkand region during 2021, 2022, and 2023. Seeds were sown in two seasons— spring and autumn—across different planting schemes (45×30 cm, 60×30 cm, and 90×30 cm). Germination capacity and phenophases were carefully monitored to determine optimal planting times. Despite the importance of seed germination timing, no detailed studies or reliable data were available from either local or international sources concerning the sowing time’s effect on seed germination of Origanum tyttanthum L. To address this gap, this research focused on evaluating how sowing periods influence seed germination under local field conditions. Findings from these studies will support successful introduction and cultivation of this medicinal plant, contributing to the biodiversity and pharmaceutical raw material base in the Samarkand oasis. This work provides a foundation for further research and sustainable use of Origanum tyttanthum L. in the region
Keywords: Origanum tyttanthum; medicinal plant; introduction